An assessment of a large-scale HIV prevention programme for high-risk men who have sex with men and transgenders in Andhra Pradesh, India: using data from routine programme monitoring and repeated cross-sectional surveys. Issue 4 (8th April 2013) - Goswami, Prabuddhagopal; Rachakulla, Hari Kumar; Ramakrishnan, Lakshmi; Mathew, Shajan; Ramanathan, Shreena; George, Bitra; Adhikary, Rajatashuvra; Kodavalla, Venkaiah; Rajkumar, Hemalatha; Paranjape, Ramesh S; Brahmam, G N V
Abstract : Objectives: To assess a large-scale intervention, the Avahan intervention, using an evaluation framework that included programme coverage, condom use and changes in sexually transmitted infection (STI) and HIV prevalence among high-risk men who have sex with men/transgender (HR-MSM/TG) in the state of Andhra Pradesh, India. Design: Programme monitoring data and results from two rounds of cross-sectional integrated biological and behavioural assessment (IBBA) in 2006 (Round 1) and 2009 (Round 2) were used for current analysis. Setting: Programme monitoring data and cross-sectional surveys from Andhra Pradesh, India. Participants: Data from 1218 and 1203 participants in Rounds 1 and 2 of the IBBA, respectively, and field level programme monitoring data from the intervention districts. Primary and secondary outcomes: (1) Assess the reach of intervention in the HR-MSM/TG population; (2) evaluate the association between intervention and the intermediate outcomes (such as condom use and STIs) and (3) assess the association between HIV/STIs and the intervention. Results: By July 2008, the intervention contacted 83% of the estimated HR-MSM/TG population monthly and 16% were attending the STI clinic monthly. HR-MSM/TG exposed to the intervention were significantly more likely to use condom consistently with a regular male partner (adjusted OR 4.62, 95% CI 1.40 to 15.22). Consistent condom use with all types of male partners increased significantly in survey Round 2 compared with Round 1. The proportion of HR-MSM/TG who tested positive for HIV-1 antibodies was similar in both rounds (15.5% in Round 1 vs 17.3% in Round 2, p=0.52). Conclusion: The Avahan intervention achieved a good population coverage, and delivered high-intensity peer and STI clinical services in Andhra Pradesh in the highly mobile target population of HR-MSM/TG; this also resulted in positive behavioural outcomes including increased condom use. However, the high prevalence of HIV in this group is an important public health priority.